Changes in Magnitude and Variability of Corticospinal Excitability During Rewarded Time-Sensitive Behavior - Suzuki, Makoto; Suzuki, Takako; Wang, Yin-Jung; Hamaguchi, Toyohiro (Frontiers in Behavioral Neuroscience, 2019)
Reward expectation and time estimation are important for behavior and affect corticospinal excitability. This study investigated changes in corticospinal excitability during rewarded time-sensitive behavioral tasks. The rewarded time-sensitive task comprised three fixed-ratio (FR) schedules: FRA contained a reward stimulus after every response, FRB after every two responses, and FRC after every four responses. The participants were instructed to press a left button with the index finger as quickly as possible in response to the appearance of a red circle. Just after the left button press, the word “10-yen” (approximately $0.1) or “no pay” was presented as feedback. Then, the participant had to mentally estimate/wait for 2.5 s from pressing the left button to pressing the right button. One second after the reward stimulus, transcranial magnetic stimulation was delivered to the primary motor cortex at the hotspot of the first dorsal interosseous muscle. Each participant received items corresponding to the total monetary reward accumulated at the end of the experiment. The variability of motor evoked potential amplitudes transformed from a random process during the resting state into an autoregressive process during the rewarded time-sensitive behavioral task. Additionally, the random variation of motor evoked potential amplitudes in the FRC, FRB, and FRA schedules increased in a stepwise fashion. However, the magnitude of motor evoked potential amplitudes significantly increased for the FRB and FRC schedules compared to the FRA schedule. The time estimation lag was negative for the three FR schedules but there was no difference among the three FR schedules. The magnitude of corticospinal excitability before reward presentation increased in low reward probability, whereas the variability of corticospinal excitability transformed into an autoregressive process in high reward probability. These results imply that the magnitude and variability of expectation-related corticospinal excitabilities can be differentially altered by reward probability.